Miary zrównoważonej karty wyników jako kryteria wyboru w decyzjach operacyjnych - Nadolna, Bożena (Measures of Balanced Scorecard as Criteria of Choices in Operative Decisions, 2008)
The operative management is closely connected with strategy because it specifies and verifies particular strategic conceptions. One of the realization tools of these conceptions is Balanced Score- card. Measurements done With this card give the opportunity to transform strategic targets on operative purposes. What is more, adapted measures in Balanced Scorecard can help in decision-making process. The aim of the article is to point out the opportunity to use Balanced Scorecard for criteria of choices in operative decisions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 289-297